2018
DOI: 10.1016/j.jmb.2017.11.008
|View full text |Cite
|
Sign up to set email alerts
|

Reduction of Nonspecificity Motifs in Synthetic Antibody Libraries

Abstract: Successful antibody development requires both functional binding and desirable biophysical characteristics. In the current study, we analyze the causes of one hurdle to clinical development, off-target reactivity, or nonspecificity. We used a high-throughput nonspecificity assay to isolate panels of nonspecific antibodies from two synthetic single-chain variable fragment libraries expressed on the surface of yeast, identifying both individual amino acids and motifs within the complementarity-determining region… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
75
2

Year Published

2018
2018
2022
2022

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 53 publications
(82 citation statements)
references
References 43 publications
5
75
2
Order By: Relevance
“…The need for glycine and phenylalanine in HCDR3 is consistent with the fact that both residues are commonly observed in the CDRs of human antibodies (37) and are expected to be important for affinity (phenylalanine) and CDR structure and flexibility (glycine). However, the lack of enrichment of these residues in AF1 is also consistent with previous observations that enrichment of these residues in antibody CDRs is linked to reduced specificity (32,34,44).…”
Section: Nature-inspired Anti-amyloid Antibodiessupporting
confidence: 91%
“…The need for glycine and phenylalanine in HCDR3 is consistent with the fact that both residues are commonly observed in the CDRs of human antibodies (37) and are expected to be important for affinity (phenylalanine) and CDR structure and flexibility (glycine). However, the lack of enrichment of these residues in AF1 is also consistent with previous observations that enrichment of these residues in antibody CDRs is linked to reduced specificity (32,34,44).…”
Section: Nature-inspired Anti-amyloid Antibodiessupporting
confidence: 91%
“…Moreover, these residues are abounded in Abs' paratopes and are unusually exposed at the molecular surface (Mian et al, 1991;Robin et al, 2014;Sundberg and Mariuzza, 2002;. In a recent study, it was demonstrated that the presence of motifs rich of Trp in CDR H3 is associated with a greater degree of antigen binding promiscuity as assessed by PSR assay (Kelly et al, 2018). This work was based on interrogation of single-chain variable fragment libraries expressed on the surface of yeast cells.…”
Section: Amino Acid Composition Of Cdr Loops 1) Number Of Charged Amimentioning
confidence: 99%
“…Several types of polyspecificity reagents have been developed for eliminating non-specific variants and enabling the isolation of antibodies with specificities that rival those of natural antibodies [37, 38]. For example, one particularly effective polyspecificity reagent is composed of soluble membrane proteins generated from mammalian cell lysates [34, 37, 39, 40]. Negative selections performed with this polyspecificity reagent and positive selections performed with the target antigen led to the isolation of antibodies with greatly reduced levels of non-specific binding relative to antibodies obtained without negative selections [37].…”
Section: Antibody Affinity/specificity Trade-offsmentioning
confidence: 99%
“…The fact that measurements of antibody specificity (non-specific binding and self-association) are the best biophysical descriptors of the likelihood of antibody success in the clinic [67] highlights the importance of developing computational and bioinformatics methods for predicting antibody specificity. Some of the key factors that determine antibody specificity are becoming clearer, including the numbers of charged, hydrophobic and hydrophilic residues in CDRs [26, 27, 39, 41, 42, 44, 6870] as well as the net charge of the variable regions [46, 47, 49]. However, methods are needed to collectively describe these disparate findings and provide guidelines for identifying antibody variants with high specificity based only on their amino acid sequences or their combined sequences and structures.…”
Section: Future Directionsmentioning
confidence: 99%